Aplikasi Pengenalan Koleksi Museum Lampung Berbasis Android - Shafina Azzahra; Febi Eka Febriansyah (Jurnal Komputasi, 2019)
Lampung Museum is the largest museum in Lampung Province, in the formation of the history of Lampung Province so that its existence needs to be preserved. currently information technology is needed in every field. the number of visitors to the Lampung Museum 2011-2017 reached 70,000 visitors. In this study the application of the Introduction to Lampung Museum Collection based on Android can increase the interest of the Lampung community as well as foreign tourists to visit and see the Museum collection, the application is equipped with a barcode scan facility that allows visitors to search collection information. The results of the study have been successfully built an "Introduction to Museum Lampung Collection Application" which has a museum collection menu, museum history, museum info, QR code scans, navigation, assistance, and about. The results of this study are: (1) functional testing with the Black Box Testing method obtain results as expected, (2) assessment using a questionnaire with the calculation of Likert Scale method, obtain a value of 88.2% in user friendly variables, and 85.06% in interactive variables, values included in the category "Very Good". it can be concluded that this application runs very well and can be used by the community.